2023
DOI: 10.1007/s42773-023-00257-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochar contributes to resistance against root rot disease by stimulating soil polyphenol oxidase

Shaohua Ge,
Jian Gao,
Dong Chang
et al.

Abstract: Biochar has been considered an effective approach as soil amendment for decreasing incidences of disease and regulating microbial populations in continuous-cropping soil. Although researches have extensively focused on changes of soil microbes and unbalance of nutrition in continuous-cropping soil, the relationship between soil properties and pathogens by biochar application remains poorly understood. In this study, we applied ITS ribosomal RNA gene profiling to analyze tobacco root microbiota of biochar and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Therefore, studies on the interactions among biochar, autotoxins and rhizosphere microorganisms could lay a theoretical foundation for alleviating obstacles to continuous cropping. In our previous experiments, we demonstrated that biochar regulates soil PPO activity in continuously cropped soil to suppress pathogens and decrease the incidence of root rot [ 12 ]. This conclusion aligns well with reports from previous literature [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, studies on the interactions among biochar, autotoxins and rhizosphere microorganisms could lay a theoretical foundation for alleviating obstacles to continuous cropping. In our previous experiments, we demonstrated that biochar regulates soil PPO activity in continuously cropped soil to suppress pathogens and decrease the incidence of root rot [ 12 ]. This conclusion aligns well with reports from previous literature [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tobacco straw used in this study was obtained from the Rice Research Institute of Shenyang Agricultural University, China. According to previous studies conducted in our laboratory, biochar produced at 450 °C from a laboratory muffle furnace is suitable for improving continuously cropped soil [ 12 ]. In these studies, biochar was produced in a factory; hence, we recommend that biochar be produced at 400 °C, which corresponds to an actual temperature of ∼450 °C according to the instructions of the carbonisation furnace manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations